Lead-lag relationships in an embryonic stock market: exploring the role of institutional ownership and liquidity - Arjoon, Vaalmikki; Bougheas, Spiros; Milner, Chris (Elsevier, 2016)
This paper investigates the influence of institutional ownership and liquidity on stock return relationships for an embryonic and relatively illiquid stock market. Using daily, individual stock data for Trinidad and Tobago from 2001 to 2015 and a VAR modelling approach, we find for firms of all sizes and levels of analyst coverage that the returns of more institutionally favoured stocks lead those with less institutional ownership. Distinctively, greater institutional coverage is shown not to be associated with greater liquidity, though liquidity levels do condition the influence of institutional ownership. This indicates that institutional owners have information advantages relative to other stock owners.